Judge’s Consideration of Post-Divorce Rights (‘Iddah and Mut’ah) from The Perspective of Maslahah Mursalah - Sholikhah, Amaliatus; J, Jamilah (Sakina: Journal of Family Studies, 2023)
The absence of clear regulations regarding determining the amount of post-divorce rights (‘iddah and mut’ah) in both positive and Compilation of Islamic law has resulted in the judge's consideration being needed for justice. This study aims to identify the judge’s steps in determining the difference in post-divorce rights and examine the judge's steps in determining the difference in post-divorce rights, and analyze the status of determining alimony as a result of divorce according to maslahah mursalah. This research uses empirical field research with a qualitative descriptive approach. Methods of data collection through interviews with judges of the Religious Court of Lumajang. The results of this study are that the legal basis for judges determining maintenance due to divorce is due to demands from the parties and is also a provision contained in Article 149 of the Compilation of Islamic Law. As for the judge's steps in determining it, it is by considering the economic facts of the parties and also looking at the goodness of his wife while they were married. The determination to live due to this divorce is a maslahah that occupies the maslahah dharuriyat level, including daily needs.